2020
DOI: 10.1001/jamaoncol.2020.2388
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chemotherapy With Survival in Elderly Patients With Multiple Comorbidities and Estrogen Receptor–Positive, Node-Positive Breast Cancer

Abstract: IMPORTANCE Breast cancer risk and comorbidities increase with age. Data are lacking on the association of adjuvant chemotherapy with survival in elderly patients with multiple comorbidities and node-positive breast cancer.OBJECTIVE To examine the association of chemotherapy with survival in elderly patients with multiple comorbidities and estrogen receptor-positive, node-positive breast cancer. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study included patients in the US National Cancer Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Prospective trials (63) and large retrospective cohorts (64,65) confirm the potential large benefit of adjuvant chemotherapy on BC-specific survival or overall survival mostly in ER-negative disease, irrespective of nodal status. A recent retrospective study showed OS benefit in patients aged ≥70 years with node-positive, ER-positive, HER2-negative BC, also with comorbidities, (66) despite selection bias remains a significant limitation. For luminal disease, genomic tools may identify those who might benefit from chemotherapy.…”
Section: Adjuvant Systemic Therapymentioning
confidence: 99%
“…Prospective trials (63) and large retrospective cohorts (64,65) confirm the potential large benefit of adjuvant chemotherapy on BC-specific survival or overall survival mostly in ER-negative disease, irrespective of nodal status. A recent retrospective study showed OS benefit in patients aged ≥70 years with node-positive, ER-positive, HER2-negative BC, also with comorbidities, (66) despite selection bias remains a significant limitation. For luminal disease, genomic tools may identify those who might benefit from chemotherapy.…”
Section: Adjuvant Systemic Therapymentioning
confidence: 99%
“…The current study indicates that a greater proportion of postmenopausal women are recommended for and receive chemotherapy as compared to the earlier study (38% vs. 28%). This finding likely reflects the knowledge that older patients derive the same degree of risk reduction from chemotherapy as their younger counterparts 6 . However, within our study population, older age remains a significant factor in predicting patients who are less likely to be offered chemotherapy despite adjustment for tumour characteristics.…”
Section: Discussionmentioning
confidence: 56%
“…This effect persisted also for patients with increased comorbidity score (HR 0.74, 95% CI 0.59-0.94). Tamirisa et al showed that adjuvant chemotherapy was associated with survival in a propensity matched cohort of patients with node-positive, HR+HER2-breast cancer who were ≥70 years with Charlson/Deyo comorbidity score ≥2 [27]. From the data available in NCDB however, it is impossible to estimate excess deaths attributable to breast cancer as opposed to uncaptured comorbid status or other determinants of health.…”
Section: Discussionmentioning
confidence: 99%